PENGARUH PERSEPSI KUALITAS, HARGA, REPUTASI PERUSAHAAN DAN KEPUASAN PELANGGAN TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN JASA PENERBANGAN LION AIR PADA PT. VINA TOUR & TRAVEL MEDAN - Sagala, Roslinda (UNIKA Santo Thomas, 2017)
The purpose of this study analyzed the influence of perceptions of quality, price, corporate reputation and customer satisfaction partially and simultaneously to the decision to purchase airline services. Benefits Research, provide empirical evidence on the influence of variables that can influence purchasing decisions from consumers and provide solutions in the form of suggestions on the management of these variables. For the community. provide knowledge to the public especially for those who want to be involved in the business world and related to the business of maintaining the brand and maintain the existence of customers. For education, it gives academic contribution to the importance of managing variables that can influence consumer purchasing decisions through the perception of quality, price, company reputation and customer satisfaction. Number of sample 96 respondents, data collection method through questioner and documentation, method of data analysis with multiple regression. Result of regression equation: PKP = 12,034 + .624 PK 0,873H + 0,505RP + .705KP. . meaning that the perception variable of quality, price, reputation of company and customer satisfaction have positive influence to decision of purchasing service of flight. Of the four variables that are more influential on the decision to purchase airline services are price variables and customer satisfaction. The correlation coefficient of perception variable of quality, price, reputation of company and customer satisfaction to decision of purchasing service of aviation have very strong relation with value value r = 0,843. The determinant coefficient of r2 = 0,710629, meaning variable variable of perception of quality, price, company reputation and customer satisfaction can explain 71,06% to decision of purchasing service of flight, while 28,94% influenced by other factors. Based on t test, the value of t count the fourth variable> t table means partially the four independent variables have a significant influence on the decision to purchase airline services. With the F test, the value of F arithmetic (Variable perception of quality, price, company reputation and customer satisfaction)> F table, meaning that simultaneously the variable has a significant influence on the decision to purchase airline services. Based on the results of research, the company should improve the perception of quality through improving the quality of service and reputation of the company through the improvement of the attributes offered through its products. Customer satisfaction and price become the center of attention from customers, then the management should still be able to maintain it for the sake of the survival of PT. Vina Tour & Travel Medan in the future.